The edge of democracy: collective choices, democratic order and institutions - Alain Herscovici (Geografares, 2023)
Based on the seminal works of Condorcet and Arrow, this paper will demonstrate why, theoretically, social choices are determined by the moral and ethical standards of the collective rather than reflecting individual wills. From this perspective, I will demonstrate why democratic regimes and their institutions are at risk from extremist social groups that challenge the Social Choice mechanism. First, I will define the concept of order in its social, economic, and political dimensions, and I will highlight the limitations of individual rationality as a regulating factor. Next, I will explain how and why collective choices must restrict certain individual liberties. Finally, I will use these concepts to (a) identify the inherent weaknesses of most democratic regimes and (b) precisely define the current threats.
Keywords: social choice; institutions; democracy; social order